2023
DOI: 10.3390/nu15040962
|View full text |Cite
|
Sign up to set email alerts
|

Severe Dyslipidemia Mimicking Familial Hypercholesterolemia Induced by High-Fat, Low-Carbohydrate Diets: A Critical Review

Abstract: Emerging studies in the literature describe an association between high-fat, low-carbohydrate diets and severe hypercholesterolemia consistent with the levels observed in patients with (homozygous) familial hypercholesterolemia (FH). High levels of low-density lipoprotein cholesterol (LDL-C) may result from the reduced clearance of LDL particles from the circulation, the increased production of their precursor, or a combination of both. The increased intake of (saturated) fat and cholesterol, combined with lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 61 publications
1
6
0
Order By: Relevance
“…Previous studies have reported lower, higher, or similar apoB or LDL-C 5 , 6 , 8 , 9 , 10 , 11 , 12 , 24 , 25 levels in individuals consuming a LCHF diet. These conflicting findings may be due to study design, short duration of observation, and lack of uniform diet composition, reflecting variations in quantity and quality of carbohydrate and fat intake.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Previous studies have reported lower, higher, or similar apoB or LDL-C 5 , 6 , 8 , 9 , 10 , 11 , 12 , 24 , 25 levels in individuals consuming a LCHF diet. These conflicting findings may be due to study design, short duration of observation, and lack of uniform diet composition, reflecting variations in quantity and quality of carbohydrate and fat intake.…”
Section: Discussionmentioning
confidence: 82%
“…This may help explain the observed clinical heterogeneity in lipid level responses among individuals on carbohydrate-restricted diets encountered in clinical practice. 8 , 9 , 10 , 11 , 12 , 13 …”
Section: Discussionmentioning
confidence: 99%
“…Conversely, excessive fruit intake can lead to the accumulation of uric acid precursors, increasing glyconeogenesis and the pentose phosphate pathway, ultimately resulting in elevated serum uric acid levels and renal dysfunction. Dietary recommendations for individuals with dyslipidemia often involve reducing macronutrient intake, particularly carbohydrates [ 42 ]. As grains are a primary source of carbohydrates, reducing their consumption is typically advised to manage dyslipidemia.…”
Section: Discussionmentioning
confidence: 99%
“…However, a systematic review examining protein diets in T2D did not conclusively confirm this effect ( 34 ). Additionally, it is crucial to note that individuals at risk of developing dyslipidemia should steer clear of a diet high in fat ( 35 ), although the composition of fats may influence this risk ( 36 ). The disparities observed between the T2D and ND groups regarding the benefits of transitioning from carbohydrates to other macronutrients may, to some extent, be influenced by the greater variation in HbA1c levels among individuals diagnosed with T2D.…”
Section: Discussionmentioning
confidence: 99%